2012
DOI: 10.5688/ajpe7610200
|View full text |Cite
|
Sign up to set email alerts
|

An Evidence-Based Course in Complementary Medicines

Abstract: Objective. To evaluate the impact of an evidence-based course in complementary medicines on the attitudes, knowledge, and professional practice behavior of undergraduate pharmacy students. Design. A required 12-week evidence-based complementary medicine course was designed and introduced into the third-year undergraduate pharmacy curriculum. The course included a combination of traditional lectures, interactive tutorial sessions, and a range of formal assessments. Assessment. Pre-and post-course survey instrum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…[ 55 , 65 , 70 , 71 , 73 78 ]. In Australia, the quest for CM education in pharmacy training started a number of years ago [ 40 , 63 , 79 ]. However, the depth and breadth of CM content varies between Australian pharmacy schools.…”
Section: Discussionmentioning
confidence: 99%
“…[ 55 , 65 , 70 , 71 , 73 78 ]. In Australia, the quest for CM education in pharmacy training started a number of years ago [ 40 , 63 , 79 ]. However, the depth and breadth of CM content varies between Australian pharmacy schools.…”
Section: Discussionmentioning
confidence: 99%
“…13,15,16 Several examples of course implementation in pharmacy curriculum and evaluation of students exist, with outcomes showing positive changes in students' knowledge of, attitudes and perceptions toward, and likelihood of recommending evidence-based complementary medicine or natural products. [17][18][19][20] In addition, students wanted more training on complementary medicine and earlier rather than later in the curriculum. 15,17 Community pharmacies have been identified by consumers as a common place to obtain vitamin supplements and natural products, and consumers expect pharmacists to be knowledgeable about these agents to offer advice.…”
Section: Introductionmentioning
confidence: 99%
“…[9] Multiple studies have shown that there has been a perceptive change in the attitude of students in medicine/allied health sciences after the course has been taught in their curriculum. [101112] Therefore, the scope and application of complementary medicine can be easily integrated with mainstream medical curriculum to enable the students to have some knowledge about alternative therapies.…”
Section: Introductionmentioning
confidence: 99%